In situ fabrication of Al3Ti-Al functionally graded composites by centrifugal casting. (2nd August 2010) - Chen, T.J.; Li, J.; Li, Y.D.; Hao, Y.
In situ Al3Ti-Al functionally graded composite rings were fabricated by centrifugal casting. The effects of processing parameters on the microstructures and hardness of the rings were mainly investigated. Simultaneously, the corrosion characteristics of the composites were discussed. The results indicated that not only the Al3Ti platelet concentration distributed with a gradient along the radial direction of the rings, but also their size appeared in a gradient distribution. The presence of Al3Ti platelets decreased the corrosion resistance of Al and the corrosion resistance of the rings also appeared in a graded manner.